Overview of the Prosocial Behavior of Volunteers of the East Java Muhammadiyah Disasster Management Center (MDMC) for Victims of the Semeru Eruption: Gambaran Perilaku Prososial Relawan Muhammadiyah Disasster Management Centre (MDMC) Jawa Timur Bagi Korban Erupsi Semeru - Ulfah, Tri Megawati; Hazim, Hazim (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe the prosocial behavior of volunteers and also to find out what factors influence the prosocial behavior of East Java MDMC volunteers involved in the response to the Mt. Semeru eruption disaster in Lumajang. The population in this study was 488 people and the sample used was 202 people based on an error rate of 5% in the table developed by Isaac and Michael. The data collection technique in this study used a psychological scale, namely a prosocial scale in the form of a Likert scale. The results of the validity test obtained as many as 34 valid items from the 44 items compiled. The reliability test obtained a result of 0.953. This study uses descriptive statistical analysis with a quantitative approach. The results showed that the prosocial of East Java MDMC volunteers who were involved in the response to the Mount Semeru eruption disaster in Lumajang, showed that most of the volunteers showed prosocial levels in the moderate category, which was as much as 80%. Volunteers who have a high prosocial level have a percentage of 6%, while volunteers who have a low prosocial level have a percentage of 14%. The factors that influence prosocial are motivated by the desire to help each other, eliminate unpleasant feelings when seeing other people need help, understand what others need in difficult circumstances to achieve goals, help individuals because there are still family relationships, and protect from threats against others. status and characteristics within the group.